Dinamika Permasalahan Laut Tiongkok Selatan & Tantangan Serius terhadap Ide Poros Maritim Dunia - Wishnu Mahendra Wiswayana (Andalas Journal of International Studies (AJIS), 2016)
In recent years situation on the South China Sea facing an escalationcondition, especially affected from China maritime activities. That conditionemerged when China put South China Sea territory at China's official map,which called 9/10/11 dashed line or u-shaped line. This paper addresses theIndonesian Government respond about territorial disputes with China'sofficial map on Natuna. The U-shaped line at China's official map actuallybecame challenges for Global Maritime Axis idea and Indonesia foreignpolicy under Jokowi-JK administration.Keyword: Global Maritime Axis, South China Sea, Foreign Policy